2008
DOI: 10.1016/j.bcmd.2008.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation and the function of CCAAT enhancer binding protein alpha (C/EBPα)

Abstract: CCAAT enhancer binding protein alpha (C/EBPα) is the founding member of a family of basic region/leucine zipper (bzip) transcription factors and is a master regulator of granulopoiesis. It is expressed at high levels throughout myeloid differentiation and binds to the promoters of multiple myeloid-specific genes at different stages of myeloid maturation. Profound hematopoietic abnormalities occur in mice nullizygous for C/EBPα̤ including a selective early block in the differentiation of granulocytes. Mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…C/EBP family proteins share highly homologous C-terminal dimerization (leucine zipper) domains and DNA binding [basic region (BR)] motifs but differ in their N-terminal transactivation domains and bind DNA either as homo- or heterodimers (21). C/EBPα has been reported to play critical roles in lineage-specific gene regulation in several cell types during hepatic, adipogenic, granulocytic, skin, lung and placenta development (22).…”
Section: Introductionmentioning
confidence: 99%
“…C/EBP family proteins share highly homologous C-terminal dimerization (leucine zipper) domains and DNA binding [basic region (BR)] motifs but differ in their N-terminal transactivation domains and bind DNA either as homo- or heterodimers (21). C/EBPα has been reported to play critical roles in lineage-specific gene regulation in several cell types during hepatic, adipogenic, granulocytic, skin, lung and placenta development (22).…”
Section: Introductionmentioning
confidence: 99%
“…4B). The bZIP domain can be further divided into the DNA binding domain and the leucine zipper domain, which is needed for interaction with other transcription factors, such as PU.1, GATA1, RUNX-1, and p21 waf1/cip1 (30). We showed that mutation in Arg-297, Lys-298, and Arg-300 (collectively, these mutants are called BR3 (31)) eliminated C/EBP␣-driven transcription activity, whereas deletion of the leucine zipper domain only reduced C/EBP␣-driven transcription activity by half.…”
Section: Basophils Might Use Different Transcription Factors From Thomentioning
confidence: 99%
“…Post-translational modifications of C/EBP␣ often occur as the result of signaling activation and have been shown to regulate C/EBP␣ functions (30). Timchenko and co-workers (35) demonstrated that PI3K signaling activated a phosphatase, pp2a, which in turn dephosphorylated C/EBP␣ at Ser-193.…”
Section: Pi3k Signaling and Calcium Signaling Pathways Are Required Fmentioning
confidence: 99%
“…Post-transcriptional modifications such as phosphorylations, SUMOylations, and acetylations have been shown to affect C/EBPb activity (Ramji & Foka 2002, Berberich-Siebelt et al 2006, Cesena et al 2008, Khanna-Gupta 2008. For instance, EGF simulation in vitro has been shown to repress transcription of COX2 via sumoylation of C/EBPb (Wang et al 2008), as opposed to the other documented role of C/EBPb in promoting COX2 transcription (Hsu et al 2010).…”
Section: Post-transcriptional Modificationsmentioning
confidence: 99%